MODERN PATHOGENETIC FEATURES OF THE COURSE AND CLINICAL AND LABORATORY METHODS FOR ASSESSING VARIANTS OF THE COURSE OF PRIMARY TUBERCULOSIS IN CHILDREN AND ADOLESCENTS - Abdukhakimov B.A.; Kudratova Z.E. (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Relevance: In the context of political changes, socio-economic instability and increased population migration due to local conflicts, the proportion of chronic processes that have the status of socially significant diseases is increasing. One of these diseases is tuberculosis.